Severe impact on family planning programme due to COVID-19 pandemic in urban population - Maiti, Debmalya; Patra, Kajal Kumar; De, Ritam; Vedika Agarwal; Kishore P Madhwani (Asian Journal of Medical Sciences, 2023)
Background: Contraception and sexual health are a fundamental human right and an integral part of women’s health services. Postpartum period is the unique opportunity for counseling and availing contraception. COVID-19 pandemic hindered routine and special services like postpartum clinics has negative impact on family planning services. Aims and Objectives: The objective of study was to compare the change in contraceptive services due to COVID-19 in two consecutive financial years (2019–2020 and 2020–2021) at Nil Ratan Sircar Medical College and Hospital, Kolkata, West Bengal, India. Materials and Methods: An institution-based, retrospective, and cohort study was carried out in Nil Ratan Sircar Medical College and Hospital among the users of contraceptive services at the department of family planning for the financial year 2019–2020 and 2020–2021. During the period, 226,700 beneficiaries attended department of family planning for the financial year 2019–2020 and 98,584 beneficiaries attended department of family planning for the financial year 2020–2021. Template was generated in MS excel sheet and analysis was done on SPSS software. Results: During the year 2019–2020, 94.73% availed combined oral contraceptives while in the year 2020–2021, 93.97% availed combined oral contraceptives. Lap ligation was decreased by 96.42%, post-abortion ligation was decreased by 85%, Interval IUCD was decreased by 79.62% and PAIUCD was decreased by 76%. During the year 2019–2020, OCP was used by the maximum beneficiaries, that is, 219,654 while in the year 2020–2021 OCP was used by 97,353 beneficiaries. Conclusion: During COVID-19 pandemic, family planning services suffer a huge setback as it is does not came under emergency services. With the ongoing COVID-19 crisis and continuous need for contraception, there is a need to refocus and motivate eligible couples for long-acting reversible contraceptive methods with significantly lower failure rates.